The Role of Digital Transformation in Education in the Development of Digital Culture among Female Public-School Students and the Obstacles They Encounter from Their Teachers’ Point of View - Assaf, Hanan Obaidullah Okleh (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to identify the role of digital transformation in education in the development of digital culture among female public-school students and the obstacles from the teachers’ point of view in the Directorate of the University Brigade in the capital, Amman. Methods: The study utilized the descriptive survey method. Two questionnaires were prepared to answer the study questions. The first questionnaire aimed to understand the role of digital transformation in education in developing the digital culture of female students in government schools, consisting of 15 paragraphs. The second questionnaire aimed to identify the obstacles to the development of digital culture among female students, consisting of 14 items. Results: The study’s findings indicated that the role of digital transformation in education in developing digital culture among female public-school students was highly regarded by the teachers. Conversely, female teachers’ estimations of obstacles to developing digital culture among female public school students were low. The results also demonstrated that there were no statistically significant differences in the teachers’ estimates of the role of digital transformation in education in developing digital culture among female public school students based on the variables of academic qualification and teaching experience. Conclusions: It is recommended to focus on enhancing the capabilities of female public-school students in designing educational platforms.